The Synthesis and Role of β-Alanine in Plants - Parthasarathy, Anutthaman; Savka, Michael A.; Hudson, André O. (Frontiers in Plant Science, 2019)
Most studies on amino acids are focused on the proteinogenic amino acids given their essential roles in protein synthesis among other pathways. In addition to the 20 ubiquitous amino acids used in protein synthesis, plants synthesize over 250 non-proteinogenic amino acids that are involved in the synthesis of compounds that are anti-herbivory, anti-microbial, response to abiotic stresses, nitrogen storage, toxins against both vertebrates/invertebrates, and plant hormones among others. One such non-proteinogenic acid in β-alanine, which is known mainly from studies on humans. β-Alanine forms a part of pantothenate (vitamin B5), which is incorporated into the universal carbon shuttling compounds Coenzyme A and acyl carrier protein, in all organisms including plants. The focus of this review however is on the biosynthesis, metabolism, and role of β-alanine in plants. There are several functions of β-alanine unique to plants. It is accumulated as a generic stress response molecule involved in protecting plants from temperature extremes, hypoxia, drought, heavy metal shock and some biotic stresses. There is evidence of its participation in lignin biosynthesis and ethylene production in some species. It is further converted to the osmoprotective compound β-alanine betaine in some species and converted to the antioxidant homoglutathione in others. The polyamines spermine/spermidine, propionate and uracil have been shown to be precursors of β-alanine in plants. However, plants vary in terms of their biosynthetic pathways and the primary metabolism of β-alanine is far from settled.